Amorphized graphene: A stiff material with low thermal conductivity. (July 2016) - Mortazavi, Bohayra; Fan, Zheyong; Pereira, Luiz Felipe C.; Harju, Ari; Rabczuk, Timon
Abstract: All-carbon heterostructures have been produced recently via focused ion beam patterning of single layer graphene. Amorphized graphene is similar to a graphene sheet in which some hexagons are replaced by a combination of pentagonal, heptagonal and octagonal rings. The present investigation provides a general view regarding phonon and load transfer along amorphous graphene. The developed models for the evaluation of mechanical and thermal conductivity properties yield accurate results for pristine graphene and acquired findings for amorphized graphene films are size independent. Our atomistic results show that amorphous graphene sheets could exhibit a remarkably high elastic modulus of ∼500 GPa and tensile strengths of ∼50 GPa at room temperature. However, our results show that mechanical properties of amorphous graphene decline at higher temperatures. Furthermore, we show that amorphized graphene present a low thermal conductivity ∼15 W/mK which is two orders of magnitude smaller than pristine graphene, and we verify that its thermal conductivity is almost insensitive to temperature since it is dominated by phonon-defect scattering rather than phonon–phonon scattering. Finally, our results show that amorphized graphene structures present a remarkably high elastic modulus and mechanical strength, along with a low thermal conductivity, which is an unusual combination for carbon-based materials.